Mistura de sabor e violação de CP - Nishi, C. C [UNESP] (2007)
he aim of this thesis is the study of the properties of CP violation and flavor mixing in the Standard Model (SM) and in some of its extensions. We study the connection between both phenomena and their relation with the space formed by the replication of gauge multiplets, which will be called horizontal spaces, present in the models. The presence of such spaces in gauge theories is a necessary condition for the appearance of flavor mixing at the Lagrangian level. These identical multiplets can introduce new sources of CP violation, as in the mechanism of spontaneous CP violation (SCPV), and, sometimes, make difficult the analysis of the CP properties of the theory, due to the freedom to rotate the basis of such spaces. The relation between the replication of scalar multiplets and CP violation is investigated in extensions of the SM with N-Higgs-doublets. In the scalar potential of these models the necessary and sufficient conditions for explicit and spontaneous CP violation are studied and CP odd invariants, like the Jarlskog invariant in the SM, are found. In these class of models, the SCPV mechanism is illustrated in the 2-Higgs- and 3-Higgs-doublet models, and the restrictions imposed by the suppression of flavor changing neutral currents are also exposed. The soft CP violation is illustrated in a model based in the gauge group SU(3)L x U(1)N nd it is shown that it can accommodate the phenomenology of the CP violation of the neutral kaons system even when the CKM mechanism is switched off and all CP violation effects are mediated by exotic fermions. The flavor mixing phenomenon is investigated through neutrino flavor oscillations from the perspective of classical relativistic field theories taking localization aspects intoaccount to search for new effects and observable deviations from the usual oscillation formulas...